Sindbis Virus Vectors Designed To Express a Foreign Protein as a Cleavable Component of the Viral Structural Polyprotein - Thomas, John M. (American Society for Microbiology, 2003)
Alphavirus-based expression vectors commonly use a duplicated 26S promoter to drive expression of a foreign gene. Here we describe an expression strategy in which the foreign sequences are linked to the gene encoding the 2A protease of foot-and-mouth disease virus and then inserted in frame between the capsid and E3 genes of Sindbis virus. During replication, the 2A fusion protein is synthesized as a component of the viral structural polyprotein that is then released by intramolecular cleavages mediated by the capsid and 2A proteases. Recombinant Sindbis viruses that expressed fusion proteins composed of 2A linked to the green fluorescent protein (GFP) and to the VP7 protein of bluetongue virus were constructed. Viruses engineered to express GFP and VP7 from a duplicate 26S promoter were also constructed. All four viruses expressed the transgene and grew to similar titers in cultured cells. However, the GFP/2A- and VP7/2A-expressing viruses displayed greater expression stability and were less attenuated in newborn mice than the cognate double-subgenomic promoter-based viruses. By combining the two expression strategies, we constructed bivalent viruses that incorporated and expressed both transgenes. The bivalent viruses grew to lower titers in cultured cells and were essentially avirulent in newborn mice. Groups of mice were vaccinated with each VP7- and VP7/2A-expressing virus, and antibody responses to native VP7 were measured in an indirect enzyme-linked immunosorbent assay. Despite their genetic and phenotypic differences, all viruses induced similarly high titers of VP7-specific antibodies. These results demonstrate that 2A fusion protein-expressing alphaviruses may be particularly well suited for applications that require enduring expression of a single protein or coexpression of two alternative proteins.